Removal of nasally impacted mesiodens by maxillary vestibular transnasal approach - Mohamed Elseyoufi; Ayman Hasan Alrabiaa; Peter Tsakiris (Elsevier, 2023)
The mesiodens is rarely associated with the nasal floor. Several surgical techniques exist for the removal of nasally impacted mesiodens. This case report presents a 13-year-old male who had uneventful surgical extraction of nasally impacted asymptomatic mesiodens using a maxillary transnasal subperiosteal approach via a modified LeFort I vestibular incision. This novel technique, which requires surgical experience and expertise, is recommended due to optimal surgical access, resulting in reduced surgical time and less bone removal with a decreased risk of damage to the adjacent structures.